Knowledge Management Models. State of the Art - Jan Andreasik (Barometr Regionalny)
In this article knowledge management models are classified into the following groups: 1. Resource models. 1.1. Holistic models. 1.2. Pyramidal models. 2.Process models. 2.1. Knowledge value chain models. 2.2. Branch models of organizational processes. 2.3. Spiral models. 3. Knowledge creation models. 4. Semantic models. As the summary the operationalization of knowledge management models is presented.